Remaking Appalachia : Ecosocialism, Ecofeminism, and Law - Stump, Nicholas F. (Book collections on Project MUSE., 2021)
"Environmental law has failed spectacularly to protect Appalachia from the ravages of liberal capitalism, and from extractive industries in particular. Remaking Appalachia chronicles such failures, but also puts forth hopeful paths for truly radical change"--